Pembangunan Bendungan Way Sekampung: Apakah Ada Perubahan Kondisi Sosial Ekonomi pada Masyarakat Terdampak Pembebasan Lahan : Studi Kasus di Kecamatan Pagelaran Kabupaten Pringsewu - Viki Ardela Viki Ardela (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
The purpose of this research is to find out the changes before and after the construction of the Way Sekampung Dam in Pagelaran District to the social and economic conditions of the community. The method used in this study is a descriptive method with a quantitative approach and using primary data. The samples used, taken based on the Purposive Sampling technique in communities affected by land acquisition, totaled 79 respondents based on the Slovin formula. The analytical tool used in this study was the Wilcoxon Signed Rank Test, because the data in this study was not distributed normally. The results showed that there was a significant difference between the economic and social conditions of the communities affected by land acquisition in Pagelaran District before and after the construction of the Way Sekampung Dam. Keywords: Economic Conditions; Social Conditions; Way Sekampung Dam.